Prioritized scheduling scheme for critical and non-critical information packets - Aanandha Saravanan, K; P. Suresh, Dr (International Journal of Engineering and Technology, 2018)
The process of energy saving mechanisms is been utilized by proper planning to transmit both critical clip and non-real infor-mation by reading overheads there by reducing throughput and bandwidth in large scale critical clip networks. The existing bundle sched-uling mythologies usedÂ Â were based on the First -in First-out (FIFO) manner in such cases the critical information at particular instant cannot be processed quickly but proposed system is designed in such a way it consists ofÂ three tier precedence structure .the critical in-formationÂ bundles are placed in the higher status prioritizing queue and processed immediately and sent to the destination node where oth-er information bundles are given less precedence on the basis of position for non critical information bundles. The proposed scheme, ener-gy efficient in reducing the number of transmission by using merger technique. The lowest precedence bundles are processed after the higher precedence bundles. The proposed algorithm proves its uniqueness based on end -to-end delay than Energy efficient wake up scheduling MAC (EEWS) and Traffic Adaptive MAC protocol (TAMAC)Â Â